A Meta-Analysis of the Effectiveness of Digital Technology-Assisted STEM Education - Feyyaz Öztop (Universitas Pendidikan Indonesia, 2023)
The purpose of this study was to reveal the effect of digital technology-assisted STEM (Science, technology, engineering, and mathematics) education on academic achievement. To achieve this purpose, experimental studies, including pre-test and post-test, were examined by meta-analysis. The study's data were obtained from 34 studies that met the inclusion criteria due to the searches made in the Databases of the National Thesis Center of the Council of Higher Education, where Turkey's postgraduate theses are located. Effect sizes of 38 comparisons were calculated from these studies. The study calculated effect sizes based on Cohen’s d coefficient. The effect size obtained after the analysis was found to be d=2.582. This finding shows that STEM education assisted by digital technology greatly affects academic achievement. In addition, a significant difference was found between the effect sizes in the study according to the level of education and the subject discipline of academic achievement. This research is expected to contribute to educational practice and future research.